2015
DOI: 10.1093/ofid/ofv186
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Outcomes of Clostridium difficile Infection in the Intensive Care Unit: A Systematic Review and Meta-Analysis

Abstract: We found that ICU setting is associated with higher Clostridium difficile infection (CDI) prevalence than general hospital population and 25% among CDI cases in ICU develop pseudomembranous colitis. CDI also affects adversely overall hospital mortality, ICU and overall hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 36 publications
5
38
1
5
Order By: Relevance
“…The prevalence of CDI exploded between the mid-1990s and mid-2000s, including community, hospital, and intensive care unit (ICU)-related disease. 6,7,[17][18][19][20] Patients with SS often have multiple risk factors associated with CDI and thus represent a high-risk population for developing CDI. 7 Our findings are consistent with the suggestion that individuals with SS are at a higher risk of developing CDI.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CDI exploded between the mid-1990s and mid-2000s, including community, hospital, and intensive care unit (ICU)-related disease. 6,7,[17][18][19][20] Patients with SS often have multiple risk factors associated with CDI and thus represent a high-risk population for developing CDI. 7 Our findings are consistent with the suggestion that individuals with SS are at a higher risk of developing CDI.…”
Section: Discussionmentioning
confidence: 99%
“…Although several metaanalyses comparing PPIs and H2RAs showed no difference in the rate of nosocomial pneumonia, [5][6][7] several large observational studies have suggested an increased risk of pneumonia with PPIs relative to H2RAs. 15,16 Similarly, although observational studies have suggested an association between the use of PPIs and C. difficile-associated diarrhea, 14,17 the risk of this problem with use of H2RA appears to be lower. 16,18 Therefore, although risks of stress ulcer prophylaxis do exist with acid-suppressive therapies, these risks may be lower with H2RAs.…”
Section: Point Counterpoint Should We Continue To Use Stress Ulcer Prmentioning
confidence: 99%
“…In contrast, the incidence of C. difficile-associated diarrhea acquired during the ICU stay was 2% (95% CI 1%-2%) in a systematic review of 22 observational studies involving a total of 80 835 ICU patients. 15 Reported rates of ventilator-associated pneumonia vary widely with the study and definition used, but are likely about 13% (95% CI 11%-16%) in adults. 16 In the absence of compelling evidence of benefit and with uncertainty about the magnitude of the harms, clearly we should de-adopt routine stress ulcer prophylaxis for critically ill children and adults.…”
Section: The "Con" Sidementioning
confidence: 99%
“…Based on five studies with over 10,000 patients, C. difficile infection patients had an average ICU stay of 24 days and overall hospital stay of 50 days compared to 19 days and 30 days, respectively, for the nonC. difficile infection group (p = 0.001) [114].…”
Section: Clostridium Difficile Infection In the Intensive Care Unitmentioning
confidence: 99%